Density, Viscosity and Refractive Index of the Ternary System (Ethanol + N-Hexane +3-Methyl Pentane) at 20, 30, 40 °C and 101.325 Kpa - Mohammed, Ghazwan A.; Oudah, Maryam Kh. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
Experimental densities, viscosities η, and refractive indices nD data of the ternary  ethanol+ n-hexane + 3-methyl pentane system have been determined at temperatures 293.15,303.15 and 313.15 K and at atmospheric pressure then these properties were calculated theoretically by using mixing rules for densities, viscosities and refractive indices .After that the theoretical data and the experimental data were compared due to the high relative errors in viscosities an equation of viscosity was proposed to decrease the relative errors.